Podwójnie zapośredniczony konterfekt. O autokreacji i jej weryfikacji na przykładzie korespondencji Józefa Pilcha - Szkaradnik, Katarzyna (Zagadnienia Rodzajów Literackich, 2021)
In the article the question of constructing an image through epistolography is discussed based on the examples of Józef Pilch — a bibliophile and historian amateur from Ustroń in Cieszyn Silesia. The volume of his correspondence was published on the occasion of 25th anniversary of his death in 2020. The authoress proves that his portrait is doubly mediated — firstly, in the letters received by the article’s hero, secondly, in the idea of the editor who chose to emphasize the unusual side to Pilch’s personality — and she ruminates over whether the editor’s idea was well-founded. She considers relations between self-creation (self-presentation) and authenticity in order to point out that the recipient’s authority at last decides about the sender’s portrait. Especially when — like in the case of the analyzed correspondence — one deals with a relational subject and the dominance of forming and sustaining bonds between people on other functions of epistolography. It turns out to be crucial in the context of Pilch’s image, because he sometimes created it by means of other people’s phrases and autobiographical patterns, and notably because it was verified by the others — not only in their answers for letters, but first of all during meetings and direct communication with the sender. Finally the authoress considers several aspects of Pilch’s creation of his own archive — on the basis of which the volume’s editor built the image of the self-taught humanist from Ustroń.